Do Leadership Style and Organizational Culture Matter for Internal Control Effectiveness? - Tyagita Dianingtyas Sudibyo; Nur Afifah; Angga Kurniawan (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to analyze the influence of leadership style and organizational culture on the effectiveness of the internal control system at the Sambas Regency Inspectorate. Using a quantitative approach, the research employed a saturated sampling technique with a total of 34 respondents consisting of inspectors and all employees. Data were collected through questionnaires and analyzed using the SmartPLS program. The results show that: (1) The dominant leadership style applied is participative; (2) Participative leadership style has a positive and significant effect on the effectiveness of the internal control system (p-value 0.041); (3) Organizational culture also has a positive and significant effect on the effectiveness of the internal control system (p-value 0.000); (4) Collectively, leadership style and organizational culture positively influence the effectiveness of the internal control system. These findings emphasize the importance of participative leadership and a supportive organizational culture in strengthening internal control systems within government supervisory institutions.